Circulating Angiogenic Factors in a Pregnant Woman on Intensive Hemodialysis: A Case Report. Issue 1 (23rd February 2016) - Akbari, Ayub; Hladunewich, Michelle; Burns, Kevin; Moretti, Felipe; Arkoub, Rima Abou; Brown, Pierre; Hiremath, Swapnil
Background: Pregnancy in patients on chronic hemodialysis therapy, though unlikely, does happen rarely. Intensive hemodialysis is thought to offer a better survival advantage to the unborn child. Circulating angiogenic factors are helpful for prognostication of pregnant patients with chronic kidney disease who are not on dialysis. Data on their utilization in dialysis patients, however, are limited. Case Presentation: We report the case of a patient with a history of interstitial nephritis who had a kidney transplant that failed after 8 years due to membranous nephropathy. She was initiated on hemodialysis three sessions per week and conceived after being on dialysis for 6 weeks. She was switched to intensive hemodialysis at 8 weeks of gestation and had a C-section because of hypertension at 35 weeks, with delivery of a healthy girl weighing 2012 g. Serum angiogenic factors (placental growth factor and soluble fms-like tyrosine kinase) were measured at 32, 33, and 34 weeks of gestation and at 1, 2, and 3 weeks postpartum. Serum angiogenic factors were similar to what has been reported for patients with chronic kidney disease and were not consistent with preeclampsia. Conclusions: Our case report expands on the literature regarding intensive hemodialysis and angiogenic factor utilization in pregnant dialysis patients. Our case report suggests that starting intensive dialysis early in pregnancy is safe and concentration of angiogenic factors are similar to those reported for patients without kidney disease, except for PIGF levels, which are somewhat higher.